Kolaborasi dan Produktivitas Pengarang Artikel Jurnal Khizanah Al-Hikmah: Jurnal Ilmu Perpustakaan, Informasi, dan Kearsipan Tahun 2013 – 2020 - Liswa Hayani; Nining Sudiar; Vita Amelia (Udayana University Press bekerjasama dengan Fakultas Ilmu Budaya Universitas Udayana, 2022)
The purpose of this research is to find out how the level of collaboration and productivity of the author in the Khizanah Al-Hikmah Journal article: Journal of Library, Information and Archive Science 2013-2020 UIN Alauddin Makassar. The population and sample in this study were all articles published in the journal Khizanah Al-Hikmah Journal: Journal of Library, Information and Archive Science in the last eight years 2013-2020. The method used in this research is descriptive quantitative research with a quantitative approach. The results of this study indicate that the results show that the number of articles from 2013-2020 was 142 articles. The average collaboration level is 0.40. The number of authors was 245 people. The most productive authors are Taufik Mathar and Tupan with 7 articles. We found that the top 5 agencies contributing to articles were UIN Alauddin Makassar (25.31%), Padjajaran University (13.47%), PDII LIPI (11.84%), Sunan Kalijaga State Islamic University (6.53%), Brawijaya University (4.9%). Affiliates with public status are 95.51% and private 4.49%. It can be concluded that most of the articles were written collaboratively, namely 56 articles, most of the writers' affiliations came from institutions of higher education libraries (81.63%).